Impacts of Covid‐19 School Closures on School Food Service Revenue: Analysis of Public Local Education Agencies in Maryland. (24th February 2023) - Zafari, Zafar; Cohen, Juliana F.W.; Sessom‐Parks, Leslie; Lessard, Donovan; Cooper, Michele; Hager, Erin
ABSTRACT: Background: The public health policies and school closures in response to the Covid‐19 pandemic have created disruptions in school meal programs. Research is needed to understand the changes in school food service revenue before and during the initial Covid‐19‐related school shutdowns. Methods: A longitudinal cohort study examining federal and state reimbursements as well as sales revenues for all public local education agencies (LEAs) in Maryland from school years (SY) 2018‐2019 and 2019‐2020 was conducted. Monthly changes in federal and state reimbursements for Child Nutrition Programs, including the National School Lunch Program (NSLP), School Breakfast Program (SBP), Summer Food Service Program (SFSP), and Child and Adult Care Food Program (CACFP) were examined. Results: In the SY 2018‐2019, the total revenues from federal and state reimbursements for SBP, NSLP, SFSP, and at‐risk CACFP were 272.9 million; in comparison, for the SY 2019‐2020, the total revenues were 241.8 million (11.4% reduction from SY 2018‐2019). On average, the school shutdown (during March to June 2020) was associated with a 450, 385 ( p ‐value < .01) reduction in federal and state reimbursements per LEA‐month (41% reduction). Conclusions: The school shutdown during the Covid‐19 pandemic was associated with a statistically significant reduction in school food service revenues across Maryland's public LEAs.